1989
DOI: 10.1111/j.1365-2125.1989.tb03494.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of nitrendipine and cilazapril alone, and in combination in hypertensive patients with chronic renal failure.

Abstract: 1. It has been reported that calcium antagonists lower blood pressure more effectively in salt replete hypertensive patients with a low plasma renin activity (PRA), whereas angiotensin converting enzyme (ACE) inhibitors are more effective in salt depleted patients with a high level of PRA. An inverse relationship between the antihypertensive effects of these two groups of drugs might therefore be expected. 2. Since salt retention and inappropriately high levels of PRA are said to contribute to hypertension in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The combination of a calcium antagonist and an ACE inhibitor may be useful in the treatment of hypertension, since in some studies an ACE inhibitor plus a calcium antagonist reduced blood pressure more than either drug alone (Brouwer et al 1985;Gennari et al 1989;quazzi et al 1984;Kloke et al 1989;Singer et al 1987). There are some reports describing that coadministration of a calcium antagonist with an ACE inhibitor has additive pharmacodynamic effects without pharmacokinetic interactions.…”
Section: Calcium Channel Antagonistsmentioning
confidence: 95%
“…The combination of a calcium antagonist and an ACE inhibitor may be useful in the treatment of hypertension, since in some studies an ACE inhibitor plus a calcium antagonist reduced blood pressure more than either drug alone (Brouwer et al 1985;Gennari et al 1989;quazzi et al 1984;Kloke et al 1989;Singer et al 1987). There are some reports describing that coadministration of a calcium antagonist with an ACE inhibitor has additive pharmacodynamic effects without pharmacokinetic interactions.…”
Section: Calcium Channel Antagonistsmentioning
confidence: 95%
“…[8][9][10] Furthermore, it has been found that when the two drug classes are given in combination they have an additive effect. [11][12][13][14][15] Randomised clinical controlled studies have shown that the combination of the two drug classes is associated with significant antihypertensive effect and is well-tolerated. [16][17][18][19] The combination of these two classes is rational, since they have complementary mechanisms of action.…”
mentioning
confidence: 99%